The Impact of Tax Information Exchange and Foreign Direct Investment on Indonesia’s Tax Revenue (2019–2023) - Kusairi, Suhal; Wulandari, Wulandari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia faces significant tax revenue losses due to cross-border tax evasion, prompting increased international cooperation and investment inflows to strengthen fiscal capacity. This study aims to examine how Automatic Exchange of Information, Exchange of Information on Request, Spontaneous Exchange of Information, and Foreign Direct Investment influence Indonesia’s tax revenue from 2019 to 2023. A quantitative approach was employed, using panel data from 34 Regional Tax Offices, analyzed through a fixed effects model to account for regional variations. The findings reveal that Automatic Exchange of Information significantly boosts tax revenue by 0.118% per additional case, Spontaneous Exchange of Information contributes a 0.092% increase per case, and Foreign Direct Investment drives a 4.2% revenue rise per unit increase. However, the Exchange of Information on Request shows no significant impact due to limited case activity. The study concludes that enhancing technological infrastructure for Automatic Exchange of Information and providing targeted training for Exchange of Information on Request can optimize tax compliance. These measures, combined with balanced Foreign Direct Investment policies, strengthen Indonesia’s fiscal framework, supporting sustainable economic growth and global transparency goals.